PENGARUH INDEPENDENSI TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI PADA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN UBUD - I Komang Angga Saputra; I Wayan Sudiana; I Putu Deddy Samtika Putra (UNHI Press, 2020)
Fraud is a deliberate action by the parties who are not responsible for governance in order to personally gain profit. The purpose of this research is to know the influence of independence against fraud prevention with internal control system as moderation variable. The location of this research was conducted on LPD Ubud district. The population in this study was all LPD employees in Ubud district amounting to 382 employees from 32 LPD. The sampling method in this research is the purposive sampling method, resulting in a sample amounting to 124 people from 32 LPD. The analytical techniques in this study are using the Moderated Regression Analysis (MRA). The test results showed that independence had no significant effect on the prevention of fraud with a parameter coefficient value of 0.048 with significance level of 0.564 > 0.05. And the independent interaction with the internal control system was positively and significantly significant to the fraud prevention with a parameter coefficient value of 0116 with significance rate of 0.018 < 0.05.